1993
DOI: 10.1002/jlb.53.2.190
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-activating factor–induced calcium mobilization and oxidative metabolism in hepatic macrophages and endothelial cells

Abstract: Fluorescence image analysis of the calcium sensitive dye Indo-1 was used to characterize platelet-activating factor (PAF)-induced calcium mobilization in hepatic macrophages and endothelial cells. PAF, but not lyso-PAF, an inactive analog, induced a rapid and transient increase in intracellular levels of calcium that appeared to depend on the presence of extracellular calcium. In both macrophages and endothelial cells, these effects were dose dependent, reaching maximal levels with 10 nM PAF. However, the kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…It has, moreover, been shown that PAF stimulated perfused liver, isolated Kupffer and hepatic endothelial cells to release superoxide anion [55,56]. These observations are in accordance with our results, which showed oxidative stress occurrence through increased production of MDA in the liver tissue.…”
Section: Discussionsupporting
confidence: 96%
“…It has, moreover, been shown that PAF stimulated perfused liver, isolated Kupffer and hepatic endothelial cells to release superoxide anion [55,56]. These observations are in accordance with our results, which showed oxidative stress occurrence through increased production of MDA in the liver tissue.…”
Section: Discussionsupporting
confidence: 96%
“…PAF is thought to act in a paracrine and autocrine manner to amplify and propagate early stages of the inflammatory response. PAF released from macrophages stimulates phagocyte chemotaxis and oxidative metabolism (141, 142). In the lung, PAF mediates ozone-induced airway inflammation, microvascular leakage, and edema (143, 144).…”
Section: Macrophage-derived Proinflammatory/cytotoxic Mediators Implimentioning
confidence: 99%
“…Whereas the oxidase of phagocytes generates large quantities of ROS that are necessary to eliminate engulfed microorganisms, the NADPH oxidase of non-phagocytic cells generates low levels of ROS that appear to have a cell signaling function. ROS generation by endothelial cells has been observed after stimulation by acetylcholine (15), interleukin-4 (16), interleukin-1 (17), interferon-␥ (17), bradykinin (18,19), platelet-activating factor (20), vascular endothelial growth factor (21), tumor necrosis factor (22)(23)(24)(25), angiotensin II (26,27), and thrombin (28). In several circumstances, this ROS production has been shown to result from activation of endothelial NADPH oxidase (24,27,28).…”
mentioning
confidence: 99%